La (des) profesionalización del trabajo social - Nogués Sáez, Luis; Martín Estalayo, Maribel (2022)
One of the intellectual concerns of our colleague Manuel Gil Parejo was to analyze the process of institutionalization of social work throughout the history of our country. From his last publication in this journal, a strong idea emerges and forms out starting point: Social work is intimately linked to its context and it is not possible to speak of a single professional model. Therefore, the aim of our contribution is to join the discussion regarding the tension between the elements of institutional recognition of social work in a postmodern and commodified context and the identifiable strategies-positions-models of social intervention.
Una de las preocupaciones intelectuales de nuestro compañero Manuel Gil Parejo fue analizar el proceso de institucionalización del trabajo social a lo largo de la historia de nuestro país. De su última publicación en esta revista3 se desprende una idea-fuerza de la que deseamos partir: el trabajo social está íntimamente unido al contexto y no puede hablarse de un único modelo de profesión. Por ello, el objetivo de nuestra contribución es sumarnos a ese ejercicio dialógico necesario entre los elementos de reconocimiento institucional del trabajo social en un contexto posmoderno y mercantilizado y las estrategias-posicionamientos-modelos de intervención social identificables.
Keywords: institucionalización; Mercado; Posmodernidad; profesión; trabajo social